Study guides

☆☆

Q: Is 6x 2y a linear equation?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

4x + 2y = 6

6x-2x-6xy-2x-2y4x-2y=2x-2y-14xy

At the y-intercept, x=0 .-2y = 18y = -9

If you mean: 2y = -4x-12 then y = -2x-6 and -6 is the y intercept

Substitution is used in Systems of Linear Equations. When you have two equations, such as y=3x+1 and 2y+5=9x+1, then substitution can be used. 2y could be substituted with 2(3x+1). You would have now the equation 6x+2=9x-1, which is more solvable.

Related questions

2y = 6x - 8y = 3x - 4========m(slope) = 3=========

-6x = 2y - 120 -2y -2y -2y - 6x = -120 +6x +6x -2y = 6x - 120 -2y/-2 = 6x/-2 - 120/-2 y = -3x + 60

2y - 6x = -8 You have two unknowns and only one equation. In the absence of any other information, this equation cannot be solved. What can be done is to make each unknown the subject of the equation. 2y = 6x - 8 y = 3x - 4 6x = 2y + 8 3x = y + 4 x = (y + 4)/3

6x+5k=12

2y-3x=4

Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68

6x - 2y = 22Solve for x:6x = 2y + 22x = 1/3y + 11/3Solve for y:-2y = -6x + 22y = 3x - 11You can not simplify the equations further without having one of the variables solved, or having more than 1 equation (such as a system)

-1

2y = 6x+2

Yes, it is a linear straight line equation.

36x2 - 4y2 = (6x - 2y) (6x + 2y)

-3

People also asked